An Improved Blade Vibration Parameter Identification Method considering Tip Clearance Variation. (23rd November 2021) - Zhang, Liang; Wang, Qidi; Li, Xin
Abstract : Blade tip timing (BTT) technology is the most effective means for real-time monitoring of blade vibration. Accurately extracting the time of blade tip reaching the sensors is the key to ensure the accuracy of the BTT system. The tip clearance changes due to various complex forces during high-speed rotation. The traditional BTT signal extraction method does not consider the influence of tip clearance change on timing accuracy and introduces large timing errors. To solve this problem, a quadratic curve fitting timing method was proposed. In addition, based on the measurement principle of the eddy current sensors, the relationship among the output voltage of the eddy current sensor, tip clearance, and the blade cutting magnetic line angle was calibrated. A multisensor vibration parameter identification algorithm based on arbitrary angular distribution was introduced. Finally, the experiments were conducted to prove the effectiveness of the proposed method. The results show that in the range of 0.4 to 1.05 mm tip clearance change, the maximum absolute error of the timing values calculated by the proposed method is 26.0359 us, which is much lower than the calculated error of 203.7459 us when using the traditional timing method. When the tip clearance changed, the constant speed synchronous vibration parameters of No. 0 blade were identified. The average value of the vibration amplitude is 1.0881 mm. Compared with the identification results without changing tip clearance, the average value error of the vibration amplitude is 0.0017 mm. It is proved that within the blade tip clearance variation of 0.4 to 0.9 mm, the timing values obtained by the proposed timing method can accurately identify the vibration parameters of the blade.